Comparative Nutritional Characterization of a Novel Formulated Composite Milk Alternative and a Conventional Infant Formula : (Corrected Proof) - Ani, Onuabuchi Nnenna; Ujah, Innocent Izuchukwu; Akpata, Ebere Immaculata; Oguazu, Chinenye Enoch (The North African Journal of Food and Nutrition Research, 2026)
Background: The beverage industry has experienced a substantial surge in the development of composite milk alternatives (CMAs), precipitated by shifting dietary preferences and specific nutritional requirements. However, the increasing utilization of these alternatives in infant nutrition has prompted critical inquiries regarding their nutritional adequacy and bioequivalence to standardized formulas. Aims: This study aimed to perform a comparative evaluation of the proximate, phytochemical, vitamin, and mineral profiles of a novel formulated CMA (plant-animal-based, formulated using soybean, tiger nut, peanut, cashew nut, dry fish, crayfish, and dates) against a conventional commercial infant formula (NAN). Materials and methods: Raw materials were processed, and homogenized in standardized proportions. Analytical characterization was conducted using established biochemical methods for proximate analysis and micro-/macro-nutrient quantification. Statistical significance was determined using a two-tailed unpaired Student’s t-test, assuming equal variance, with the threshold for significance set at α = 0.05. Results: Distinct compositional divergence was observed between the formulated CMA and the commercial control. The CMA exhibited significantly higher concentrations (p<0.05) of crude fiber and moisture, as well as elevated levels of bioactive phytochemicals, including phenols, flavonoids, and lycopene. Additionally, the CMA contained a more diverse array of antinutritional factors (tannin, phytate, and alkaloids), and high concentrations of vitamins B2 and C. Conversely, NAN exhibited significantly higher carbohydrate and ash content (p < 0.05), resulting in a superior total caloric density, alongside higher concentrations of vitamins B1 and B9. While most mineral concentrations were comparable, the CMA displayed significantly higher levels of sodium, cobalt, and zinc. Conclusion: The formulated CMA demonstrated a nutritional profile that compares favorably with conventional infant formula in several key metrics. While these findings suggest significant nutritional potential, further optimization and rigorous safety evaluations are imperative before this formulation can be recommended for infant consumption. Keywords: Plant-based; Composite; Milk alternative; Nutritional profile.